Patterns of evidence: Exodus [videorecording (DVD)] - Mahoney, Timothy P., 1957- (Thinking Man Films, 2015)
Did the Israelites' exodus from Egypt really happen? There's evidence that it did. Traveling from the United States to Israel and England, filmmaker Timothy Mahoney sifts through archaeological and historical clues, as well as comments from scholars and experts, to determine the truth as he builds a new case for an ancient, and often controversial, story.